In silico study of the toxicity and biological activity of 1,2,4-triazole derivatives containing a heterocyclic substituent - Safonov, A. A.; Panasenko, O. I.; Zabihailo, O.; Mormul, V.; Rotar, A .; Mashkina, K.; Сафонов, Андрій Андрійович; Панасенко, Олександр Іванович (Запорізький державний медико-фармацевтичний університет, 2023)
The aim of the work was to study the toxicity parameters and Docking analysis of pharmacological activity data of already synthesized substances in order to obtain more extensive information about the benefits of the substances for modern society.
Keywords: тези доповідей